Accelerated Access to Innovative Medicines for Patients in Need. Issue 5 (9th July 2014) - Baird, L G; Banken, R; Eichler, H‐G; Kristensen, F B; Lee, D K; Lim, J C W; Lim, R; Longson, C; Pezalla, E; Salmonson, T; Samaha, D; Tunis, S; et al.
<x xml:space="preserve">Abstract</x> There is broad agreement among health‐care stakeholders that more must be done to ensure that patients have timely access to new and innovative medicines. Assuming that industry will continue to develop such medicines at a sustainable rate, regulators and payers become the gatekeepers. Regulators, starting in the late 1980s/early 1990s, and, more recently, payers have implemented a variety of early‐access pathways or initiatives, and this practice is continuing even today. This article describes the specific approaches that have been taken in four economically developed regions, reviews their success rates, and suggests possible new directions. Clinical Pharmacology & Therapeutics (2014); 96 5, 559–571. doi:10.1038/clpt.2014.145